‘See what you feel’: The impact of visual scale distance in haptic-to-visual crossmodal matching - Olga Daneyko; Francesca Frisco; Angelo Maravita; Daniele Zavagno (i-Perception)
Two experiments were conducted to explore the impact of the distance of a visual scale employed in the crossmodal matching method dubbed See What You Feel (SWYF) used to study the Uznadze haptic aftereffect. Previous studies reported that SWYF leads to a general underestimation of out-of-sight handheld spheres, which seems to increase with visual scale distance. Experiment 1 tested the effect of visual scale distance in haptic-to-visual crossmodal matching. A 19-step visual scale, made of actual 3D spheres (diameters ranging from 2.0 to 5.6 cm), was set at one of three possible distances (30, 160, 290 cm); participants’ task was to find the matching visual spheres for four out-of-sight handheld test spheres (diameters 3.0, 3.8, 4.6, 5.0 cm). Results confirmed the underestimation effect and only partially confirmed the role of scale distance. Experiment 2 investigated the role of scale distance in a visual-to-visual matching task in which the same visual scale was employed, set at one of three distances (37, 160, 290 cm). Participants’ task was to find a match for the same four test stimuli. Results showed no statistical difference between matched and actual sphere sizes with distance 37 cm; underestimations were observed with the far distances, thus reflecting overestimations of scale sphere sizes. Results from both experiments allow us to conclude that the underestimation effect observed with SWYF is a general feature of haptic-to-visual crossmodal matching, and that the SWYF method is a valuable tool for measuring haptic size perception with handheld stimuli when the visual scale is set at a visually comfortable peripersonal distance.